Global health education programming as a model for inter-institutional collaboration in interprofessional health education. Issue 4 (July 2014) - Peluso, Michael J.; Hafler, Janet P.; Sipsma, Heather; Cherlin, Emily
Abstract While global health (GH) opportunities have expanded at schools of medicine, nursing, and public health, few examples of interprofessional approaches to GH education have been described. The elective GH program at our university serves as an important opportunity for high-quality interprofessional education. We undertook a qualitative study to examine the experience of student, faculty and administrative leaders of the program. We used content analysis to code responses and analyze data. Among the leadership, key themes fell within the categories of interprofessional education, student–faculty collaboration, professional development, and practical considerations for the development of such programs. The principles described could be considered by institutions seeking to develop meaningful partnerships in an effort to develop or refine interprofessional global health education programs.